Measurements of 50 Non-polar Organic Compounds Including Polycyclic Aromatic Hydrocarbons, n-Alkanes and Phthalate Esters in Fine Particulate Matter (PM2.5) in an Industrial Area of Chiba Prefecture, Japan - Yujiro Ichikawa; Takehisa Watanabe; Yasuhide Horimoto; Katsumi Ishii; Suekazu Naito (Asian Journal of Atmospheric Environment, 2018)
Quantitative data of 50 non-polar organic compounds constituting PM2.5 were continuously collected and analyzed from June 2016 to October 2017 (approximately 17 months) at Ichihara, one of the largest industrial areas in Japan. Target nonpolar organic compounds including 21 species of polycyclic aromatic hydrocarbons (PAHs), 24 species of n-alkanes and 5 species of phthalate esters (PAEs) were simultaneously measured by gas chromatography/mass spectrometry. Basically, the average concentrations of the total PAHs, n-alkanes and PAEs in each season remained nearly level, and seasonal variations were little throughout the study period. These results suggest that the emission sources, which are not influenced by the seasons, are the dominant inputs for the target organic compounds. Diagnostic ratios of PAHs, assessment of n-alkane homologue distributions, carbon preference index, and the contribution of wax n-alkanes from plants were used to estimate source apportionments. These results indicate that anthropogenic sources were the main contributor for most PAHs and n-alkanes throughout the study period. The concentrations of PAEs selected in this study were low because emission amounts of these chemicals were little within the source areas of the sampling site. To our knowledge, this study is the first attempt to simultaneously measure a high number of non-polar organic compounds in PM2.5 collected from the ambient air of Japan, and the resultant data will provide valuable data and information for environmental researchers.